La hidrarquía en las costas del Darién extranjeros, colonos y cunas entre 1739-1800 - Vásquez Pino, Daniela (Universidad Santiago de Cali, 2020)
This chapter describes and analyzes the geopolitical dynamics of the Darien province during the 18th century, especially how the presence of foreigners on the coasts of the province and their economic and social relationship with the Cunas, indigenous to this territory, influenced the decisions policies of the Spanish colonists and military who inhabited the region during this season. The intention is to locate these relationships as a consequence of the political agency of the Cunas and not as a cause, as has been argued in other works, and how this agency allowed to keep the Darién away from the materialization of the policies proposed on paper and in the magnifying glass of the geopolitical interests of different European nations